2023
DOI: 10.1097/mrr.0000000000000573
|View full text |Cite
|
Sign up to set email alerts
|

Short-term and long-term predictors of balance function in stroke patients: a 6-month follow-up study

Abstract: We aimed to determine early predictors of balance function (Berg Balance Scale, BBS) at 3 and 6 months after stroke using clinical, neurophysiological, and neuroimaging variables. Seventy-nine patients with hemiparesis after a stroke were included. Demographics, stroke characteristics, and clinical variables [Mini-Mental State Examination, BBS, strength in the hemiparetic hip, knee, and ankle muscles, and Fugl-Meyer Assessment Lower Extremity (FMA-LE)] were evaluated 2 weeks poststroke, on average. Somatosenso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…We found that muscle strength, cognitive function, the presence of CIP/CIM, the primary diagnosis cerebral disease, and depression were the key factors associated with balance. This is partly in line with previous study results, as higher muscle strength was also reported as an independent predictor for enhanced balance function in patients with chronic stroke 26 and in older hip fracture patients after motor rehabilitation 75 . However, no such association was found in healthy individuals 76 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that muscle strength, cognitive function, the presence of CIP/CIM, the primary diagnosis cerebral disease, and depression were the key factors associated with balance. This is partly in line with previous study results, as higher muscle strength was also reported as an independent predictor for enhanced balance function in patients with chronic stroke 26 and in older hip fracture patients after motor rehabilitation 75 . However, no such association was found in healthy individuals 76 .…”
Section: Discussionsupporting
confidence: 92%
“…Hence, it is essential to tackle balance impairments. Alongside balance training, targeting factors linked to balance (such as muscle strength, cognitive function, and mental health 26 28 ) may provide an opportunity for enhancing balance. However, neither balance nor associated factors were so far evaluated in ICU survivors.…”
Section: Introductionmentioning
confidence: 99%
“…In the first capture, a straight position offers values lower than 5 • , while in the second capture there is a marked trunk swing with angles greater than 35 • (in this case, the pose has been forced for simulating a strong swing of the trunk). 15 9 of 22 patient. For instance, a person who needs to use the arms to get seated probably should get a worse score than who does not need them.…”
Section: Controlled Laboratory Testsmentioning
confidence: 99%
“…Once the problem of falls has been exposed and contextualized, it is important to review the clinical tools available to assess this risk. In the recent literature, the most used methods are the Tinetti test [ 13 , 14 ], the Berg scale [ 15 , 16 ], the Dynamic gait index [ 17 , 18 , 19 ], the test timed up-and-go (TUG) [ 20 , 21 ], the four-square test [ 22 , 23 ], the functional reach test [ 24 , 25 ], and the single leg stance test [ 26 , 27 ]. All of them have in common that they require the presence of a therapist responsible for evaluating and supervising the process [ 28 ].…”
Section: Introductionmentioning
confidence: 99%